Cold War Civil Rights : Race and the Image of American Democracy - Dudziak, Mary L., 1956- (Book collections on Project MUSE., 2011)
In 1958, an African-American handyman named Jimmy Wilson was sentenced to die in Alabama for stealing two dollars. Shocking as this sentence was, it was overturned only after intense international attention and the interference of an embarrassed John Foster Dulles. Soon after the United States' segregated military defeated a racist regime in World War II, American racism was a major concern of U.S. allies, a chief Soviet propaganda theme, and an obstacle to American Cold War goals throughout Africa, Asia, and Latin America. Each lynching harmed foreign relations, and "the Negro problem" became.